Integrasi Sufisme Dan Psikologi Transpersonal Dalam Pembentukan Kesehatan Mental - Mufidah, Wardatul; Chintya Dewi, Windy; Maliki Abitolkha, Amir (Universitas Darul Ulum, 2023)
Transpersonal psychology recognizes mystical experience as a fundamental element in the development of human consciousness. Sufism, representing the Islamic tradition of mysticism, provides a pathway of psychological transformation through the stages of fana’—the dissolution of ego—and baqa’—the attainment of stable spiritual awareness. This research critically explores the interrelation between Sufism and transpersonal psychology by identifying conceptual parallels between fana’ and Maslow’s idea of self-transcendence, as well as between baqa’ and Jung’s notion of individuation. Through a critical literature review, this study reveals that mystical experiences within Sufism are not merely spiritual occurrences but function as psychological processes that contribute to emotional regulation, self-identity reconstruction, and the enhancement of mental well-being. Moreover, Sufi contemplative practices such as muraqabah and dhikr share significant similarities with mindfulness techniques in contemporary psychotherapy, highlighting their potential therapeutic value. The findings suggest that integrating Sufi principles with transpersonal psychology could reshape modern psychotherapeutic paradigms, promoting a more holistic and spirituality-oriented model of mental health intervention.